2001
DOI: 10.1002/app.2219
|View full text |Cite
|
Sign up to set email alerts
|

Morphology monitoring of PE/PBT blends by reactive processing

Abstract: Polyethylene (PE)/poly(butylene terephthalate) (PBT) blends were in situ compatibilized during a processing operation by the addition of a partially hydroxylated ethylene vinyl acetate copolymer (EVAh). This copolymer, obtained from ethylene vinyl acetate (EVA), was as compatible with PE as EVA was before modification. In the presence of EVAh, the dispersion of PBT in the PE matrix was finer, and the interfacial adhesion was improved. These results are relevant for the compatibilization of PE/PBT blends. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Effect of reactive compatibilisation on the morphology, [13][14][15][16][17][18][19][20] mechanical, [21][22][23][24][25][26] crystallization, 27 rheological, 28 -30 dynamic mechanical, 31 and barrier 32,33 properties were reported extensively in literature. George et al 13 have reported that maleic anhydride (MA) containing compatibiliser improved the 'interfacial condition' and, thereby, reduced the dispersed phase size and provided more uniform particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of reactive compatibilisation on the morphology, [13][14][15][16][17][18][19][20] mechanical, [21][22][23][24][25][26] crystallization, 27 rheological, 28 -30 dynamic mechanical, 31 and barrier 32,33 properties were reported extensively in literature. George et al 13 have reported that maleic anhydride (MA) containing compatibiliser improved the 'interfacial condition' and, thereby, reduced the dispersed phase size and provided more uniform particle size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the acrylic acid moieties enhance the polarity of the EAA, and thus result in its compatibilization with the PETG. 20 Therefore, after incorporating the EAA into the HDPE/PETG blends, the EAA played the role of a bridge between the HDPE matrix and the PETG domains so as to improve their interfacial adhesion, and made the PETG-rich domains to be drawn into continuous laminar structures by the HDPE matrix much better than that in the absence of the EAA.…”
Section: Effect Of Eaa On Morphologymentioning
confidence: 99%
“…In addition, it is known that strong intermolecular interaction between the PETG and the EAA was reported in the literature. 20 These miscibility and strong intermolecular interaction may be responsible for the positive deviation in the melt viscosity of the ternary blends. …”
Section: Rheological Propertiesmentioning
confidence: 99%
“…Poly (butylene terephthalate) (PBT) sees wide application in such industries as automobile, electrical and electronics, and limited application for its poor low-temperature impact toughness and big notch sensitivity at room temperature [1][2][3][4] . These days, rubber (elastomer) and inorganic fibers are added together into the polymer to form the three-phase compound system, with a view to gain the high-performance low-cost compound material with the increased strength and toughness.…”
Section: Introductionmentioning
confidence: 99%